Analisis Ibrani 11:1 dan Penerapannya dalam Kehidupan Orang Percaya - Suci Tri Hapsari (LPPM STT Baptis Kalvari, 2022)
Hebrews 11 has been one of the most beloved passages of Scripture for centuries. It has been widely understood as the definition of faith, which is the basis of all things hoped for and the evidence of things not seen. However, this passage is not a complete discussion of what is meant by faith in Hebrews, but rather a characteristic of some key aspects of the faith of the Old Testament witnesses. Although the sentence structure fits a contemporary definition very well, modern interpreters have become hesitant to regard the verse as a formal definition of faith. The analysis of the words ὑπόστασις (substance) and ἔλεγχος (conviction) which leads to the recognition of the objective character inherent in these two words will determine the interpretation of Hebrews 11:1. Biblical faith is concerned with a firm belief in God's greater reality and vital assurance of future and unseen things, which will be revealed in God's appointed time.